2009
DOI: 10.1167/iovs.09-3717
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Retinal Ganglion Cell Death and the Neuroprotective Effects of the Calcium Channel Blocker Lomerizine

Abstract: Lomerizine had differential effects on necrotic and apoptotic death with time, but its inability to completely prevent secondary death suggests that full neuroprotection will require combinatorial treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 68 publications
6
98
0
Order By: Relevance
“…However, it did not prevent demyelination of the ON. 86,87 Minocycline Minocycline, a broad spectrum tetracycline antibiotic has been investigated as a potential treatment for primary open angle glaucoma as it has been shown to promote trabecular meshwork cell and ON head astrocyte survival. 88 This antiapoptotic effect has also been demonstrated in the RGCs of rats with glaucomatous eyes and following ON transection.…”
Section: Lomerizinementioning
confidence: 99%
“…However, it did not prevent demyelination of the ON. 86,87 Minocycline Minocycline, a broad spectrum tetracycline antibiotic has been investigated as a potential treatment for primary open angle glaucoma as it has been shown to promote trabecular meshwork cell and ON head astrocyte survival. 88 This antiapoptotic effect has also been demonstrated in the RGCs of rats with glaucomatous eyes and following ON transection.…”
Section: Lomerizinementioning
confidence: 99%
“…In the current partial ON transection study, we take advantage of the spatial separation of axons and somata undergoing primary versus secondary injury to identify, using semi-quantitative fluorescence immunohistochemistry, likely key contributors to the progression of secondary degeneration in this model. Finally, we have shown that the L-and T-type voltage-gated calcium channel blocker lomerizine is effective in reducing the amount of secondary RGC death from 2 weeks after partial ON transection (Fitzgerald et al, 2009a(Fitzgerald et al, , 2009b. Furthermore, lomerizine reduced secondary infiltration of macrophages at 7 days, and accumulation of aggregates of the oxidative stress marker manganese superoxide dismutase (MnSOD) at 1 month (Fitzgerald et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Ventral axons of the ON, which are vulnerable only to secondary degeneration, are spatially separated from neurons and glia damaged by a dorsal primary ON injury (Fitzgerald et al, 2009a;Levkovitch-Verbin et al, 2003). After transection of dorsal axons in the Piebald Virol Glaxo (PVG) rat there is both primary and secondary death of retinal ganglion cells (RGCs) in the centrodorsal retina, while RGCs in the ventral retina exclusively undergo secondary degeneration (Fitzgerald, 2009b). The separation of optic axons from their parent somata, together with spatial separation of primary from secondary degeneration across the nerve, allows a comprehensive assessment of the sequence of events contributing specifically to secondary degenerative events in CNS tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Nifedipine, verapamil, and diltiazem have been shown to be effective in normal tension glaucoma 44,45 and nilvadipine in open angle glaucoma. 46 Other calcium channel blockers, such as flunarizine and lomerizine, have shown to be effective in animal models but not in humans. 47 Calcium channel blockers should be used with caution because of their systemic hypotensive effect which may be potentially detrimental to optic nerve head perfusion.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%